The two Josephson junction flux qubit with large tunneling amplitude - Shnyrkov, V.I.; Soroka, A.A.; Melnyk, S.I. (Физика низких температур, 2008)
In this paper we discuss solid-state nanoelectronic realizations of Josephson flux qubits with large tunneling
amplitude between the two macroscopic states. The latter can be controlled via the height and form of
the potential barrier, which is determined by quantum-state engineering of the flux qubit circuit. The simplest
circuit of the flux qubit is a superconducting loop interrupted by a Josephson nanoscale tunnel junction.
The tunneling amplitude between two macroscopically different states can be essentially increased, by
engineering of the qubit circuit, if tunnel junction is replaced by a ScS contact. However, only Josephson
tunnel junctions are particularly suitable for large-scale integration circuits and quantum detectors with preset-
day technology. To overcome this difficulty we consider here the flux qubit with high-level energy separation
between «ground» and «excited» states, which consists of a superconducting loop with two lowcapacitance
Josephson tunnel junctions in series. We demonstrate that for real parameters of resonant superposition
between the two macroscopic states the tunneling amplitude can reach values greater than 1 K. Analytical
results for the tunneling amplitude obtained within semiclassical approximation by instanton technique
show good correlation with a numerical solution.